2022
DOI: 10.1155/2022/2594195
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of Some Selected Plant Species Traditionally Used as Tea in the Sharri Mountains (Kosovo)

Abstract: The study evaluates the chemical composition of the volatile constituents of ten plant species traditionally used as herbal tea in the Sharri Mountain regions (Kosovo and North Macedonia). Volatile constituents responsible for the flavour and fragrance of selected species (Crataegus monogyna, Cydonia oblonga, Malus sylvestris, Matricaria chamomilla, Morus alba, Morus nigra, Rosa canina, Sambucus nigra, Tilia cordata, and Vaccinium myrtillus) were separated and then identified using GC-MS, whereas GC-FID is emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The earlier studies found that these compounds of other origins exhibited antimalarial and antioxidant activities 48 , 49 . 1-octadecene was reported to have therapeutic applications representing potent antimalarial, antioxidants and antibacterial activities 49 , 50 . It was assumed that 1-octadecene may cause alteration in the cell membrane permeability in parasites resulting in leakage of metabolites and ions 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The earlier studies found that these compounds of other origins exhibited antimalarial and antioxidant activities 48 , 49 . 1-octadecene was reported to have therapeutic applications representing potent antimalarial, antioxidants and antibacterial activities 49 , 50 . It was assumed that 1-octadecene may cause alteration in the cell membrane permeability in parasites resulting in leakage of metabolites and ions 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Spathulenol, cis-pinocamphone (E)-caryophyllene, 1,8-cineole, caryophyllene oxide, and isomenthone were identified as the major compounds. [16] Finally, the last case studied highlighted a great richness in long-chain hydrocarbons and anisaldehyde in the dried flowers EO, and in p-menth-1-en-8-ol, geraniol, eugenol, linalool and various hydrocarbons in the dried leaves of Ukrainian C. monogyna. [17] However, in the state of art, no study was conducted on common perfumery extracts, absolutes, concretes or resinoids (definition given in Supporting Information [18] ) of hawthorn.…”
Section: Introductionmentioning
confidence: 94%